Marijuana use and viral suppression in persons receiving medical care for HIV-infection. (2nd January 2017) - Okafor, Chukwuemeka N.; Zhou, Zhi; Burrell, Larry E.; Kelso, Natalie E.; Whitehead, Nicole E.; Harman, Jeffery S.; Cook, Christa L.; Cook, Robert L.
ABSTRACT: Background : Marijuana use is common among persons living with HIV (PLWH), but studies on its effect on HIV clinical outcomes are limited. Objectives : We determined the association between marijuana use and HIV viral suppression among PLWH. Methods : Data came from five repeated cross-sections (2009–2013) of the Florida Medical Monitoring Project, a population-based sample of PLWH in Florida. Data were obtained via interview and medical record abstraction (MRA). Weighted logistic regression models were used to determine the association between marijuana use (past 12 months) and durable viral suppression (HIV-1 RNA value of ≤ 200 copies/milliliter in all measurements within the past 12 months). Results : Of the 1, 902 PLWH receiving antiretroviral therapy, completed an interview, and had a linked MRA, 20% reported marijuana use (13% less than daily and 7% daily use) and 73% achieved durable viral suppression. In multivariable analysis, marijuana use was not significantly associated with durable viral suppression in daily [Adjusted Odds Ratio (AOR): 0.87, 95% confidence interval (CI): 0.58, 1.33] or in less than daily [AOR: 0.83, 95% CI: 0.51, 1.37] users as compared to non-users when adjusting for sociodemographic factors, time since HIV diagnosis, depressive symptoms, alcohol, cigarette and other substance use. Conclusion : In this sample of PLWH receiving medical care in Florida, there was no statistically significant association between marijuana use and viral suppression. However, as the limits of the confidence intervals include effects that may be considered to be clinically important, there is a need for additional evidence from other samples and settings that include more marijuana users.